Effekte von Agrarumweltmaßnahmen und der Ausgleichszulage auf den betrieblichen Faktoreinsatz: Ergebnisse einer Propensity-Score-Matching-Analyse; Effects of Agri-Environment Programs and the Less-Favoured Area Scheme on Farm Input Use: Results from Propensity Score Matching - Andrea Pufahl; Christoph R. Weiss (German Journal of Agricultural Economics (GJAE), 2010)
– The paper applies a semi-parametric matching approach (propensity score matching) to evaluate the effects of agri-environment (AE) programs and the less-favoured area (LFA) scheme on input use (land, labour, capital, livestock, fertilizer and pesticides) and farm output of individual farms in Germany. The analysis reveals a positive and significant effect of both farm programs on the area under cultivation, in particular on grassland, resulting in a decrease of cattle livestock density. Furthermore, participation to AE programs significantly reduced the purchase of fertilisers. For both farm programs, no significant effect on farm sales is observed. Furthermore, the magnitude of program effects increases along with increasing program payments. Key words: Evaluation; agri-environment programs; less-favoured area scheme; propensity score matching
Keywords: 330